2008
DOI: 10.2147/vhrm.2008.04.01.213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term lycopene supplementation and postprandial dyslipidemia on plasma antioxidants and biomarkers of endothelial health in young, healthy individuals

Abstract: Abstract:The objective of this study was to test the hypothesis that the effect of a high-fat meal (HFm) on plasma lipid-soluble antioxidants and biomarkers of vascular oxidative stress and infl ammation would be attenuated by short-term lycopene supplementation in young healthy subjects. Following restriction of lycopene-containing foods for 1-wk (LYr), blood was collected in a fasting state and 3 h after a HFm and a low-fat meal (LFm) in N = 18 men aged 23 ± 2 years, and after a HFm only in N = 9 women aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 53 publications
0
42
0
1
Order By: Relevance
“…In particular, lycopene has been accounted for cell growth regulation through apoptosis and cell cycle inhibition [50][51][52][53][54][55], facilitation of gap junction communication [56,57], stimulation of immune system [51,[58][59][60], modulation of endocrine-mediated pathways [57,58], induction of detoxifying enzymes [61,62] and reduction of cell surface adhesion and intima-media thickness [63]. Many studies have underlined how lycopene has anti-proliferative and prodifferentiation properties; in particular, it can inhibit proliferation of several types of cancer cells, including those of prostate, breast, lung, and endometrium [58,64,65].…”
Section: Lycopene: Chemistry Biochemical Func-tions Dietary Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, lycopene has been accounted for cell growth regulation through apoptosis and cell cycle inhibition [50][51][52][53][54][55], facilitation of gap junction communication [56,57], stimulation of immune system [51,[58][59][60], modulation of endocrine-mediated pathways [57,58], induction of detoxifying enzymes [61,62] and reduction of cell surface adhesion and intima-media thickness [63]. Many studies have underlined how lycopene has anti-proliferative and prodifferentiation properties; in particular, it can inhibit proliferation of several types of cancer cells, including those of prostate, breast, lung, and endometrium [58,64,65].…”
Section: Lycopene: Chemistry Biochemical Func-tions Dietary Sourcesmentioning
confidence: 99%
“…Accordingly, Kawashina et al [221] showed that measures of oxidative stress decreased with a decline of serum lipid peroxides and of urine 8-OHdG. Dennis et al [63] instead found that a short-term supplementation did not affect either the plasma lipid-soluble antioxidant pool or the biomarkers of vascular oxidative stress and inflammation. More recently, a study on the supplementation with purified lycopene [224] confirmed that at high dose of 30 mg lycopene/day decreased DNA oxidative damage in lymphocytes and urinary 8-hydroxy-deoxyguanosine while no significant differences were observed for glucose, lipid profile and other biomarkers of lipid peroxidation.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…Neste estudo, ficou evidente uma diminuição da integridade das membranas plasmática e do retículo sarcoplasmático após o exercício. Vários experimentos comprovaram a eficiência do licopeno: na redução significativa de tumores da próstata 22 , no risco de câncer pancreático 23 , prevenção de tumores de mama 24 , redução do tamanho da próstata em hiperplasias benignas 25 , redução no risco de desenvolvimento de doenças coronarianas 26 , no controle significativo de dislipidemias 27 e na redução da indução de crises asmáticas 28 . Experimentos mostraram a eficiência do antioxidante ácido ascór-bico como um potente suplemento que aumenta a sobrevida dos cardiomiócitos e promove a neovascularização cardíaca 29 .…”
Section: Discussionunclassified
“…Four weeks of lycopene supplementation (tomato-derived Lyc-O-Mato) at 30mg·day -1 in obese patients was not found to favorably influence markers of inflammation and oxidation biomarkers, despite a significant increase in plasma cartenoids, and specifically lyopene (Markovits et al, 2009). One week of lyopene supplementation (80mg·day -1 ) was found again to increased endogenous capacity of plasma lipid-soluble antioxidants (lycopene, -carotene, and -tocopherol); however, biomarkers of vascular oxidative stress and inflammation were unaffected in the fasted state, as well as post consumption of a high fat meal, in young, healthy subjects (Denniss et al, 2008). Finally, both acute (24 hour) and long-term (seven day) tomato puree consumption had no effects on endothelial dysfunction after consumption of a meal, despite a significant increase in plasma lyopene levels in healthy postmenopausal women (Stangl et al, 2011).…”
Section: Lycopenementioning
confidence: 95%